2014
DOI: 10.1294/jes.25.37
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and Intestinal Barrier–protective Activities of Commensal Lactobacilli and Bifidobacteria in Thoroughbreds: Role of Probiotics in Diarrhea Prevention in Neonatal Thoroughbreds

Abstract: We previously isolated the commensal bacteria lactobacilli and bifidobacteria from the Thoroughbred intestine and prepared the horse probiotics LacFiTM, consisting of Lactobacillus ruminis KK14, L. equi KK 15, L. reuteri KK18, L. johnsonii KK21, and Bifidobacterium boum HU. Here, we found that the five LacFiTM constituent strains remarkably suppressed pro-inflammatory interleukin-17 production in mouse splenocytes stimulated with interleukin-6 and transforming growth factor-β. The protective effects of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…The 1 week of treatment course chosen in previous studies therefore might not be sufficient to see an effect 3, 5, 9. A treatment period of 3 weeks was chosen for this study.…”
Section: Discussionmentioning
confidence: 91%
“…The 1 week of treatment course chosen in previous studies therefore might not be sufficient to see an effect 3, 5, 9. A treatment period of 3 weeks was chosen for this study.…”
Section: Discussionmentioning
confidence: 91%
“…In equine medicine probiotics have been increasingly studied to prevent and treat disease due to few reported side effects, low cost and ease of administration [10], although clinical data are currently equivocal. Probiotics have been shown to reduce the incidence of diarrhoea in foals [11,12], but other studies have found a higher incidence of diarrhoea requiring veterinary attention in neonatal foals [13,14]. Several studies were unable to show beneficial effects of probiotic administration in prevention or treatment of diarrhoea in adult horses [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacilli have been shown to increase tight junction protein expression, consequently restoring intestinal permeability [22]. The fact that the total number of adhering bacteria was not altered by the analysed hydrolysates, nor their profile, may indicate the stability of the intestinal barrier, thus remaining the most abundantly anchored lactic acid bacteria, and that they may potentially exert a beneficial effect by their protective function and metabolic activity [23]. Bacterial adhesion is thought to play a role in the maintenance of the mucus layer by influencing the number and size of mucus secreting Goblet cells [24].…”
Section: Discussionmentioning
confidence: 99%